Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation [tex]\( 2 \log_5(3x - 2) - \log_5(x) = 2 \)[/tex], follow these steps:
1. Express the equation in terms of logarithms:
We start with the given equation:
[tex]\[ 2 \log_5(3x - 2) - \log_5(x) = 2 \][/tex]
2. Combine the logarithmic terms:
Recall the properties of logarithms:
[tex]\[ a \log_b(c) = \log_b(c^a) \][/tex]
and
[tex]\[ \log_b(a) - \log_b(b) = \log_b\left(\frac{a}{b}\right) \][/tex]
So we use the first property to rewrite [tex]\(2 \log_5(3x - 2)\)[/tex] as:
[tex]\[ 2 \log_5(3x - 2) = \log_5((3x - 2)^2) \][/tex]
Then our equation becomes:
[tex]\[ \log_5((3x - 2)^2) - \log_5(x) = 2 \][/tex]
Using the second property of logarithms, combine the logarithmic terms:
[tex]\[ \log_5\left(\frac{(3x - 2)^2}{x}\right) = 2 \][/tex]
3. Rewrite the equation in exponential form:
The equation [tex]\(\log_b(A) = C\)[/tex] is equivalent to [tex]\(A = b^C\)[/tex].
Thus, we can rewrite [tex]\(\log_5\left(\frac{(3x - 2)^2}{x}\right) = 2\)[/tex] as:
[tex]\[ \frac{(3x - 2)^2}{x} = 5^2 \][/tex]
Simplify this:
[tex]\[ \frac{(3x - 2)^2}{x} = 25 \][/tex]
4. Solve the resulting equation:
Multiply both sides by [tex]\(x\)[/tex] to eliminate the fraction:
[tex]\[ (3x - 2)^2 = 25x \][/tex]
Expand the left-hand side:
[tex]\[ 9x^2 - 12x + 4 = 25x \][/tex]
Bring all terms to one side to set the equation to zero:
[tex]\[ 9x^2 - 12x + 4 - 25x = 0 \][/tex]
[tex]\[ 9x^2 - 37x + 4 = 0 \][/tex]
5. Solve the quadratic equation:
Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 9\)[/tex], [tex]\(b = -37\)[/tex], and [tex]\(c = 4\)[/tex]:
[tex]\[ x = \frac{-(-37) \pm \sqrt{(-37)^2 - 4 \cdot 9 \cdot 4}}{2 \cdot 9} \][/tex]
[tex]\[ x = \frac{37 \pm \sqrt{1369 - 144}}{18} \][/tex]
[tex]\[ x = \frac{37 \pm \sqrt{1225}}{18} \][/tex]
[tex]\[ x = \frac{37 \pm 35}{18} \][/tex]
This gives us two possible solutions:
[tex]\[ x = \frac{37 + 35}{18} = \frac{72}{18} = 4 \][/tex]
[tex]\[ x = \frac{37 - 35}{18} = \frac{2}{18} = \frac{1}{9} \][/tex]
6. Verify the solutions:
Substitute [tex]\(x = 4\)[/tex] and [tex]\(x = \frac{1}{9}\)[/tex] back into the original equation to check for validity:
- For [tex]\(x = 4\)[/tex]:
[tex]\[ 2 \log_5(3 \cdot 4 - 2) - \log_5(4) = 2 \][/tex]
[tex]\[ 2 \log_5(10) - \log_5(4) = 2 \][/tex]
[tex]\[ 2 \log_5(10) - \log_5(4) = 2 \][/tex]
Simplifying the left-hand side confirms that the equation holds true.
- For [tex]\(x = \frac{1}{9}\)[/tex]:
Without calculation, substitute [tex]\(x = \frac{1}{9}\)[/tex] into the equation results negative arguments in the logarithms which are undefined in the real number ([3x - 2 < 0]). Therefore, this solution doesn't satisfy the original equation,
Thus, the valid solution is:
[tex]\[ x = 4 \][/tex]
1. Express the equation in terms of logarithms:
We start with the given equation:
[tex]\[ 2 \log_5(3x - 2) - \log_5(x) = 2 \][/tex]
2. Combine the logarithmic terms:
Recall the properties of logarithms:
[tex]\[ a \log_b(c) = \log_b(c^a) \][/tex]
and
[tex]\[ \log_b(a) - \log_b(b) = \log_b\left(\frac{a}{b}\right) \][/tex]
So we use the first property to rewrite [tex]\(2 \log_5(3x - 2)\)[/tex] as:
[tex]\[ 2 \log_5(3x - 2) = \log_5((3x - 2)^2) \][/tex]
Then our equation becomes:
[tex]\[ \log_5((3x - 2)^2) - \log_5(x) = 2 \][/tex]
Using the second property of logarithms, combine the logarithmic terms:
[tex]\[ \log_5\left(\frac{(3x - 2)^2}{x}\right) = 2 \][/tex]
3. Rewrite the equation in exponential form:
The equation [tex]\(\log_b(A) = C\)[/tex] is equivalent to [tex]\(A = b^C\)[/tex].
Thus, we can rewrite [tex]\(\log_5\left(\frac{(3x - 2)^2}{x}\right) = 2\)[/tex] as:
[tex]\[ \frac{(3x - 2)^2}{x} = 5^2 \][/tex]
Simplify this:
[tex]\[ \frac{(3x - 2)^2}{x} = 25 \][/tex]
4. Solve the resulting equation:
Multiply both sides by [tex]\(x\)[/tex] to eliminate the fraction:
[tex]\[ (3x - 2)^2 = 25x \][/tex]
Expand the left-hand side:
[tex]\[ 9x^2 - 12x + 4 = 25x \][/tex]
Bring all terms to one side to set the equation to zero:
[tex]\[ 9x^2 - 12x + 4 - 25x = 0 \][/tex]
[tex]\[ 9x^2 - 37x + 4 = 0 \][/tex]
5. Solve the quadratic equation:
Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 9\)[/tex], [tex]\(b = -37\)[/tex], and [tex]\(c = 4\)[/tex]:
[tex]\[ x = \frac{-(-37) \pm \sqrt{(-37)^2 - 4 \cdot 9 \cdot 4}}{2 \cdot 9} \][/tex]
[tex]\[ x = \frac{37 \pm \sqrt{1369 - 144}}{18} \][/tex]
[tex]\[ x = \frac{37 \pm \sqrt{1225}}{18} \][/tex]
[tex]\[ x = \frac{37 \pm 35}{18} \][/tex]
This gives us two possible solutions:
[tex]\[ x = \frac{37 + 35}{18} = \frac{72}{18} = 4 \][/tex]
[tex]\[ x = \frac{37 - 35}{18} = \frac{2}{18} = \frac{1}{9} \][/tex]
6. Verify the solutions:
Substitute [tex]\(x = 4\)[/tex] and [tex]\(x = \frac{1}{9}\)[/tex] back into the original equation to check for validity:
- For [tex]\(x = 4\)[/tex]:
[tex]\[ 2 \log_5(3 \cdot 4 - 2) - \log_5(4) = 2 \][/tex]
[tex]\[ 2 \log_5(10) - \log_5(4) = 2 \][/tex]
[tex]\[ 2 \log_5(10) - \log_5(4) = 2 \][/tex]
Simplifying the left-hand side confirms that the equation holds true.
- For [tex]\(x = \frac{1}{9}\)[/tex]:
Without calculation, substitute [tex]\(x = \frac{1}{9}\)[/tex] into the equation results negative arguments in the logarithms which are undefined in the real number ([3x - 2 < 0]). Therefore, this solution doesn't satisfy the original equation,
Thus, the valid solution is:
[tex]\[ x = 4 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.